RESISTANCE OF SOYBEAN GENOTYPES WITH LARGE SEED SIZE AND EARLY MATURITY AGAINST POD BORER, Etiella zinckenella TREITSCHKE - Bayu, Marida Santi Yudha Ika; Prayogo, Yusmani (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Pod borer is a major pest on soybean. The objective of this study was to determine the resistance of soybean genotypes against pod borer based on choice test. The experiment was conducted in green house and laboratory of Entomology, Indonesian Legumes and Tuber Crops Research Institute, using Randomized Block Design with 16 soybean genotypes and three replicates. Planting dates was arranged such a way so as to sincronize the flowering time and pod formation of 16 soybean genotypes. A pairs of 4 days emerged adult pod borer were infested into each plant at R4 stage (21 days after flowering) for two days. The number of egg was observed at 2 days after infestation (DAI) and the number of larva and damaged intensity were observed at 14 DAI. The results showed that genotypes significantly affected egg and larval population, pod and seed damage intensity. The lowest egg and larval population found on Anjasmoro, 6,33 eggs and 10 individuals, respectively. The lowest intensity of pod damage found on Anjasmoro (27,74%), and the lowest intensity of seed damage found on Malabar/Sinabung-68 (15,61%). The resistance of soybean genotypes was non-preference as place to lay eggs and as feed. In conclusion, there were two genotypes showed consistently resistant (Anjasmoro and Malabar/Sinabung-68). These genotypes could be used as a source of genes for varietal improvement of soybean resistance against pod borer.